Tik-Tok Application: Development Of Achievement Learning To Increase Interest In Learning At Madrasah Aliyah Negeri 1 Lampung Timur - Asy'arie, Bima Fandi (AT-TURATS, 2023)
This study aims to determine current learning activities, design learning development, and the practicality of moral creed learning development design through the TikTok application. The methods of this research are Reseach and Development (RD). Which is analysis, design, development, implementation, and evaluation. The results of this study show that the teaching of moral creed has gone well. However, the learning method still uses lectures, discussions, and memorization methods. This learning development design uses several supporting applications, such as Benime, Text Voice Free, Picsart, Kine Master dan Video ke MP3 Converter and help apps WhatsApp. Assessment of 9 validators which includes subject matter experts 83,5%, learning design expert 84,4%, learning media expert 84,4%, all are categorized as very feasible. The small group test development stage obtains 88,0%, and implementation of large-group trials of the highest gains, namely 67,7% The predicate is very appropriate. Pre-test and post-test results with an average of 90 rose 60%, So the completeness of students while learning to use Tik-Tok media 100% thoroughly. Then, the practicality test obtains an average score 4,8 with very practical categories. This shows that the development design that has been tested is very worthy of further development.